Optimized robot strategy, ball filters and new referee whistle hardware filter - Ribeiro, A. Fernando (2007)
This paper briefly describes the main changes on the Minho Team robots since the last RoboCup edition. Work has been carried out on the robots in order to constantly improve their capabilities, based on the experience from previous participations. The main topics to deal in this paper are related with the optimization of movement on the field and also game strategy software, a ball filter recently implemented on the robots in order to follow only the correct ball. Also on this paper a description of the whole software implementation is made by describing the main Algorithm. A new referee whistle hardware filter has been developed in the last year and is here described its electronics.